Preoperative criterion identifying a low‐risk group for lymph node metastasis in intrahepatic cholangiocarcinoma. (22nd May 2018) - Yoh, Tomoaki; Hatano, Etsuro; Seo, Satoru; Terajima, Hiroaki; Uchida, Yoichiro; Taura, Kojiro; Yasuchika, Kentaro; Uemoto, Shinji
Abstract: Background: Imaging study cannot identify patients with potential low‐risk for lymph node (LN) metastasis in intrahepatic cholangiocarcinoma (ICC). The purpose of this study was to identify a low‐risk group for LN metastasis in ICC using preoperatively available factors. Methods: Data from 127 consecutive patients, who underwent curative intent surgery for ICC at Kyoto University Hospital and Kitano Hospital between 2002 and 2016, were retrospectively analyzed. By using only preoperative data, multiple linear regression model for predicting LN metastasis was developed. Results: Forty‐three patients exhibited LN metastasis (33.9%). Serum CA19‐9 levels ≥37 IU/ml, ICC with hilar invasion, and LN swelling were identified as independent preoperative predictors of LN metastasis. The prediction model for LN metastasis using these three factors revealed good discrimination (area under the receiver operating characteristics curve 0.874, P < 0.001). Negative for all three factors (i.e. CA19‐9 levels <37 IU/ml, peripheral ICC and no LN swelling) identified 35 patients (27.6%) as a low‐risk group, with the false negative rate of 2.3%. Conclusions: We proposed a preoperative criterion for predicting LN metastasis, giving rise to the identification of ICC patients who showed a low‐risk of LN metastasis. Abstract : Highlight Low risk for lymph node metastasis in intrahepatic cholangiocarcinoma cannot be identified on imaging studies. Yoh and colleagues propose a prediction model with good discriminatory power based on serum CA19‐9 levels, hilar invasion, and lymph node enlargement. All three factors were negative in 27.6% of patients, constituting the low‐risk group.